Ayat-Ayat Dakwah; Kandungannya Dalam Bingkai Penafsiran Alquran - Siti Fahimah (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2020)
In the Koran, almost the majority have the content to call for an invitation to goodness or preaching, so it can be said that the invitation to kindness is the obligation of every living person to be able to imagine a goodness in society. In this study the authors focused on verses those who study about da'wah then formulate it in the title, so that this study includes more of the da'wah verses which are then explored in more elaboration with the maudhui method of interpretation and information from outside the interpretation that is very supportive of the title raised. From the titles that appear and the verses that support it show that Allah pays great attention to da'wah and for a preacher also has a guide to step in the steps of preaching so that it is right and in accordance with what is expected. In this study only disclosed which is the object of study in the subject of the interpretation of the dakwah verse and collected in 8 wetting points which begins with a discussion of the verse and is followed by a discussion that supports it.